Pengaruh Pengungkapan Corporate Social Responsibility (CSR) Dan Good Corporate Governance (GCG) terhadap Profitabilitas Perusahaan (Studi Empiris terhadap Perusahaan Pertambangan yang Terdaftar di BEI Periode Tahun 2010-2020) - Gani Saputra; Didi Sundiman; Iqbal Miftakhul Mujtahid (J-MAS (Jurnal Manajemen dan Sains), 2023)
Corporate Social Responsibility (CSR) is an effort to maintain the company's position in the competition to maintain harmony with consumers. Not only CSR, the company must also strengthen the company's internals by implementing Good Corporate Governance (GCG). CSR and GCG are able to increase the company's profitability. This underlies the purpose of the study, namely to determine the ability of CSR and GCG in influencing the profitability of mining companies listed on the IDX. One of the advantages of this thesis is that this research was carried out by observation to find out the financial statements of mining companies listed on the IDX and included in statistical analysis calculations (using the R Program) using the Panel Data Regression analysis method and tested in each variable to find out whether there is an influence between Variables. This type of research is quantitative research with secondary data on IDX financial statements as data collection. The sample in this study is a mining company listed on the Indonesia Stock Exchange (IDX) in 2010-2020 with 34 mining companies annually in accordance with the established criteria. The data analysis method used in this study is a descriptive method with a quantitative approach using panel data regression. The results of the analysis show that csr and GCG variables do not have a significant influence on ROA. In addition, the p-value has a value of (0.97) with a value higher than the significance value of 0.05. The event proved that regression modeling was incapable of explaining the ROA data. This happens because the financial performance of a company is influenced by various factors. One of the factors is that during 2019 the stock index of mining companies experienced a decline due to a decrease in coal prices. In other words, if CSR and GCG get better, the company's profitability will increase.